Impact of self-rated health among elderly on visits to family physicians - Amira Kurspahić-Mujčić; Melisa Čalkić; Suad Sivić (Medicinski glasnik, 2016)
Aim: To evaluate an impact of eight dimensions of self-rated health measured by the SF-36 questionnaire on visits to family physicians among people older than 65. Methods: This cross-sectional study was carried out in family medicine outpatient departments of the Public Institution Primary Health Care Center of Canton Sarajevo, Bosnia and Herzegovina. The study included 200 respondents divided into two age groups:18-65 (n=100) and older than 65 (n=100). The SF-36 questionnaire for self-assessment of health status and a questionnaire for the evaluation of socio-demographic characteristics of respondents and health care utilization were used. Results: In the group of respondents aged 18-65 the dimension that was related to physical functioning was assessed as best (79.1±25.6), while the dimension concerning the vitality was assessed as the worst (56.1±19.9). In the group of respondents older than 65 the dimension related to social functioning was assessed as best (65.4±24.9), and the dimensions related to general health was assessed as worst (47.7±20.4). Family physicians were visited by significantly more respondents older than 65 than those from the age group 18-65 (94% vs.74%) (p= 0.000). Scores on the scales of general health (p=0.021) and social functioning (p=0.024) in respondents older than 65 had a significant impact on visits to family physicians. Conclusion: Poor self-rated general health and better social functioning are important predictors of visiting family physicians by elderly persons.
Keywords: age; primary health care; quality of life